2003
DOI: 10.1063/1.1569986
|View full text |Cite
|
Sign up to set email alerts
|

The use of Simmons’ equation to quantify the insulating barrier parameters in Al/AlOx/Al tunnel junctions

Abstract: We have analyzed the electron transport processes in Al/AlOx/Al junctions. The samples were produced by glow-discharge-assisted oxidation of the bottom electrode. The nonlinear I–V curves of 17 samples were measured at room temperature, being very well fitted using the Simmons’ equation with the insulating barrier thickness, barrier height, and the junction area as free parameters. An exponential growth of the area normalized electrical resistance with thickness is obtained, using just values from I–V curve si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
50
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 16 publications
11
50
1
Order By: Relevance
“…Indeed, it is difficult to imagine microscopic processes that affect large areas ∼ 10nm 2 ; a more plausible explanation is that the conductance is dominated by relative small areas or channels in this system [16] which decreases further the number of fluctuators (Figure 1). This conjecture is supported by the recent analysis [17] that found that the conductive area is κ ∼ 10 −5 of the total. Most likely, however, this value depends strongly on the material preparation.…”
supporting
confidence: 77%
“…Indeed, it is difficult to imagine microscopic processes that affect large areas ∼ 10nm 2 ; a more plausible explanation is that the conductance is dominated by relative small areas or channels in this system [16] which decreases further the number of fluctuators (Figure 1). This conjecture is supported by the recent analysis [17] that found that the conductive area is κ ∼ 10 −5 of the total. Most likely, however, this value depends strongly on the material preparation.…”
supporting
confidence: 77%
“…This oxidation method was preferred given its lowest oxidation rate as compared with more sophisticated methods, such as oxygen plasma and dry oxygen methods. The former may lead to shorts and pinholes or "hot spots," 11,12 and the latter compared with the present work does not produce a more robust oxide layer as will be discussed later.…”
mentioning
confidence: 72%
“…These may even occur in experiments where advanced plasma oxidation techniques have been used. 11,12 The present work focuses on the temperature dependence of the tunneling phenomena across Al 2 O 3 . We find no appreciable variation of the barrier width as a function of temperature and a mild temperature dependence of the barrier height.…”
mentioning
confidence: 99%
“…One line fit the band gap regime, and the other the conduction band. This ln(dI/dV) linear fit method was chosen over IV or (dI/dV)/(I/V) fit methods for it's insensitivity to high noise in STS spectra [14,15]. Approximately 40-80 dI/dV spectra were taken on each sample >100 nm apart from one another in order to get reasonable statistics on the sample's surface.…”
Section: Methodsmentioning
confidence: 99%